2020
DOI: 10.1055/s-0040-1701467
|View full text |Cite
|
Sign up to set email alerts
|

Increased Sympathetic Cardiac Autonomic Modulation after Two Consecutive Tilt Tests in Women with Polycystic Ovary Syndrome

Abstract: Objective The present study aimed to analyze cardiac autonomic modulation via spectral and symbolic analysis of heart rate variability (HRV) in women with polycystic ovary syndrome (PCOS) who were subjected to two consecutive tilt tests. Methods A total of 64 women were selected and divided into 2 groups: control (without PCOS), and PCOS. Concentrations of follicle-stimulating hormone, luteinizing hormone, prolactin, estradiol, homocysteine, sex hormone-binding globulin, thyroid stimulating hormone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Similarly, a study by Ribeiro et al reported no significant fat distribution between cases and control [28]. Hyperandrogenism and Insulin resistance may contribute to increased sympathetic tone in PCOS patients rather than BMI [29].…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, a study by Ribeiro et al reported no significant fat distribution between cases and control [28]. Hyperandrogenism and Insulin resistance may contribute to increased sympathetic tone in PCOS patients rather than BMI [29].…”
Section: Discussionmentioning
confidence: 89%
“…(5)(6)(7)(8)(9) The Rotterdam criteria (2003), used for diagnosis, require 2 of the 3 aforementioned criteria, being facultative ovarian cysts. (1)(2)(3) Its diagnosis is of exclusion. Pathologies such as ovarian or adrenal tumors, hyperprolactinemia, hypo-or hyperthyroidism and Cushing syndrome can cause the same androgenic and anovulation symptoms and can mask the syndrome.…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…The diagnosis of PCOS is based on the Rotterdam criteria, characterized with hyperandrogenism, chronic anovulation and polycystic ovaries on ultrasound. (3) Excess androgen alters the regulation of female hormones, resulting in menstrual irregularity and infertility. Among its main manifestations are hirsutism, acne, seborrhea, and alopecia.…”
Section: Introductionmentioning
confidence: 99%